Reducción del costo en el consumo de energía eléctrica utilizando tecnología LED en los laboratorios de la Facultad de Ingeniería de Sistemas e Informática de la UNSM - Cabezas Fasanando, Katia Nieves (2013)
The investigation is based on the influence that the use of LED technology in cost reduction in power consumption. The investigation takes as a sign to telematics and networking laboratories of the Faculty of Engineering and Computer Systems, National University of San Martin, Tarapoto. Basically established investigation design Pre and Post Test, which consisted of measurements of the power consumption in the telematics and network laboratories, measurements are first made with fluorescent tubes and LED tubes, then comparing these measurements it was found that using LED technology significantly reduces the cost of electricity consumption, it follows that both economic saving is obtained as energy savings.